2022
DOI: 10.3390/ijerph192315849
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Correlation of Physical Activity and Tendency to Problematic Mobile Phone Use in College Students

Abstract: Objective: To explore the effect of problematic mobile phone use on college students’ physical activity and their relationships. Methods: A cross-sectional study was conducted among 3980 college students from three universities in Jiangsu province by random cluster sampling. The International Physical Activity Questionnaire Short (IPAQ-SF) measured college students’ physical activity. The Mobile Phone Addiction Tendency Scale for College Students (MPATS) measured problematic mobile phone use tendencies. Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…To the authors’ knowledge, this is the first study that investigated comparing the effects of Pilates, corrective exercises, and Alexander’s technique on upper cross syndrome among adolescent girls’ students (ages 13–16): a six-week study. The main findings of this study were [ 1 ] Six weeks of CE and AT significantly reduced FHA, RS, and kyphosis in adolescent girls with UCS; [ 2 ] PE showed a reduction in FHA, RS, and kyphosis, but this reduction was not statistically significant; [ 3 ] There was a significant difference between the FH, RS, and kyphosis of girls in the PE, CE, and AT groups, with the CE and AT groups showing greater improvements than the PE group; [ 28 ] There was no significant difference between the mean FH of girls in the CE and AT groups; [ 29 ] There was a significant difference between the PE group and both the CE and AT groups in all three variables of FH, RS, and kyphosis. These findings suggest that CE and AT may be more effective than PE in improving UCS in adolescent girls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To the authors’ knowledge, this is the first study that investigated comparing the effects of Pilates, corrective exercises, and Alexander’s technique on upper cross syndrome among adolescent girls’ students (ages 13–16): a six-week study. The main findings of this study were [ 1 ] Six weeks of CE and AT significantly reduced FHA, RS, and kyphosis in adolescent girls with UCS; [ 2 ] PE showed a reduction in FHA, RS, and kyphosis, but this reduction was not statistically significant; [ 3 ] There was a significant difference between the FH, RS, and kyphosis of girls in the PE, CE, and AT groups, with the CE and AT groups showing greater improvements than the PE group; [ 28 ] There was no significant difference between the mean FH of girls in the CE and AT groups; [ 29 ] There was a significant difference between the PE group and both the CE and AT groups in all three variables of FH, RS, and kyphosis. These findings suggest that CE and AT may be more effective than PE in improving UCS in adolescent girls.…”
Section: Discussionmentioning
confidence: 95%
“…The widespread use of electronic devices like mobile phones has become essential in daily life, especially for students [ 1 ]. Prolonged use of these devices can lead to abnormal postures, causing neuromuscular imbalances and musculoskeletal conditions [ 2 ] such as upper crossed syndrome (UCS).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that people's mobile phone habits may change during the COVID-19 pandemic [12,13]. The COVID-19 pandemic poses a certain threat to the life and safety of every individual [14]. Therefore, college students may pay more attention to negative information such as death cases, internet rumors, and shortage of epidemic prevention materials, resulting in a certain degree of information anxiety.…”
Section: Introductionmentioning
confidence: 99%